CLINICAL CASE: COMBINATION THERAPY WITH BOSENTAN AND SILDENAFIL IN THE TREATMENT OF IDIOPATHIC PULMONARY HYPERTENSION - V. V. Bystrov; O. A. Arkhipova; T. V. Martynyuk; M. A. Saidova; O. V. Stukalova; N. M. Danilov; T. A. Sakhnova; I. Ye. Chazova (Евразийский Кардиологический Журнал)
The patient with the verified diagnosis of idiopathic pulmonary hypertension, functional class III (WHO) was treated by anticoagulants, diuretics, calcium channel blocker. After one year of adding endothelin receptor antagonist bosentan there was noticed the negative dynamic with right heart chambers dilation, appearing of heart failure signs. By 11 months of the combined pathogenetic therapy with bosentan and phosphodiesterase type 5 inhibitor sildenafil there was achieved the significant improvement of the functional and hemodynamic status. This positive dynamics remained within the next 3 years of observation.